PENERAPAN TEKNOLOGI INDUSTRI 4.0 DALAM LEAN WAREHOUSING: LITERATURE REVIEW - Pangestu, Nadia Angelina Putri; Parung, Joniarto; Wibisono, Eric (Jurnal Ilmiah Teknik Industri, 2024)
Warehouse plays a crucial role in the supply chain by linking material flows between suppliers and customers, and also matching demand with product availability. Operational disruptions in warehouse can lead to decreased customer satisfaction, necessitating effective and efficient warehouse operations. Lean principles, including lean warehousing, are often used to achieve this. Additionally, increasing supply chain complexity makes companies vulnerable to costly errors, leading to broader adoption of industry 4.0 technologies. Various studies have begun integrating industry 4.0 technologies into lean warehousing practices. However, literature reviews on integrating industry 4.0 with lean principles tend to focus on manufacturing area. This study aims to review researches on the application of industry 4.0 technologies in lean warehousing through a literature review. The findings of the literature review indicate that autonomous robots, simulation, horizontal and vertical system integration, and the industrial internet of things are industry 4.0 pillars that are widely applied alongside lean warehousing methodologies and tools. Most studies analyze overall warehouse processes, while others focus on specific processes within the warehouse. Overall, the use of industry 4.0 technologies in lean warehousing leads to significant positive impacts, including increased efficiency and productivity. Further studies are needed to understand how lean warehousing can serve as a foundation for implementing industry 4.0 technologies and to address the issues and challenges in their concurrent application.